Keterampilan Bertanya Siswa Kelas Atas Sekolah Dasar dalam Pembelajaran IPAS melalui Model Inquiry Learning: Literature Review - Akmal Mutia; Desvina Aulia Rakhman; Hilleri Putri; Rolan Oktaviani Putri (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Questioning skills are one of the essential 21st-century competencies that support critical thinking, curiosity, and student engagement in learning. However, various studies indicate that elementary school students’ questioning skills are still dominated by lower-order thinking questions, highlighting the need for appropriate instructional approaches to enhance these skills. This study aims to describe the questioning skills of upper elementary school students in science and social studies (IPAS) learning, describe the implementation of the Inquiry Learning model, and analyze the relationship between Inquiry Learning and students’ questioning skills. This study employed a Literature Review method using scientific journal articles obtained from Google Scholar and Garuda databases. The article identification and selection process followed the PRISMA guidelines and resulted in eight articles that met the inclusion criteria. Data were analyzed descriptively through the stages of identification, selection, extraction, synthesis, and conclusion drawing. The findings reveal that students’ questioning skills still need to be improved to encourage more critical and in-depth questions. The implementation of Inquiry Learning through investigative activities encourages students to ask questions, seek information, and construct knowledge independently. Furthermore, the review indicates a positive relationship between Inquiry Learning and students’ questioning skills, as reflected in increased questioning activity, learning engagement, and critical thinking ability. Therefore, Inquiry Learning can be considered an effective instructional model for developing questioning skills in elementary school IPAS learning.